Implementation of Incung Script Learning as a Form of Local Wisdom-Based Curriculum Development at SD Negeri 046/XI Koto Tengah - M Nurzen; Tara Elimar; Sun Limei (P3M IAI Nusantara Batang Hari, 2022)
The incung script is an ancient script used by the indigenous Kerinci tribe as a medium of communication written on logs/bark, buffalo horns and palm leaves. The implementation of the incung script as a curriculum development based on local wisdom is an image of the community to continue to preserve culture in the form of education. The purpose of this study is to see how the process of implementing the incung script is a form of local wisdom-based curriculum development at SD Negeri 046/XI Koto Tengah. This study uses a qualitative research method with a descriptive approach to show how the implementation of the incung script in education. The result of the study shows that the implementation of the incung script as a form of local wisdom-based curriculum development goes through seven stages including: feasibility and needs study stage